2017
DOI: 10.1111/1471-0528.14521
|View full text |Cite
|
Sign up to set email alerts
|

The CAPS Study: incidence, management and outcomes of cardiac arrest in pregnancy in the UK: a prospective, descriptive study

Abstract: 25% of cardiac arrest in pregnancy is caused by anaesthesia. Rapid perimortem section improves survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 20 publications
3
87
1
10
Order By: Relevance
“…A study of UK Obstetric Surveillance System data showed that one‐quarter of maternal cardiac arrests were related to anaesthesia. Of this number, 75% of the women were obese . Epidural resite rate in the women with class III obesity (greater than 136 kg in weight) was 17% in a cohort study compared with 3% in the control group (less than 113 kg in weight) .…”
Section: Risk Assessment During Pregnancy In Women With Obesitymentioning
confidence: 99%
“…A study of UK Obstetric Surveillance System data showed that one‐quarter of maternal cardiac arrests were related to anaesthesia. Of this number, 75% of the women were obese . Epidural resite rate in the women with class III obesity (greater than 136 kg in weight) was 17% in a cohort study compared with 3% in the control group (less than 113 kg in weight) .…”
Section: Risk Assessment During Pregnancy In Women With Obesitymentioning
confidence: 99%
“…In addition, women with mechanical prosthetic heart valves are at particularly increased risk of complications in pregnancy . These women should be cared for by an appropriately skilled and experienced multidisciplinary team, usually in regional centres . Other cardiac causes include: cardiomyopathy; dissection of the coronary artery; acute left ventricular failure; infective endocarditis; and pulmonary oedema.Evidence level 2 + +…”
Section: Clinical Issuesmentioning
confidence: 99%
“…The majority of deaths secondary to cardiac causes occur in women with no previous history, 2,3 and almost one in five deaths occurred in an ambulance or accident and emergency department. 2,38 Therefore, paramedics and accident and emergency staff must be familiar with the management of maternal collapse. The main cardiac causes of maternal death are ischaemia and sudden arrhythmic cardiac death with a structurally normal heart.…”
Section: Cardiac Diseasementioning
confidence: 99%
See 2 more Smart Citations